A critical discourse analysis of Covid-19 in Iranian and American newspapers - Dezhkameh, Ali; Layegh, Nasim; Hadidi, Yaser (Penerbit Universiti Kebangsaan Malaysia, 2021)
The policies and ideologies of countries are reflected in the propagated media of that country, and newspapers are no exception. Covid-19 has affected the lives of people all around the world. The present study investigated the ideological differences in reporting the news related to Covid-19 in light of Van Dijk’s ideological square framework. To do so, a representative sample of 56 news articles was chosen over a period of one year (from January 2020 to the end of January 2021) from one Iranian and one American newspaper, the Tehran Times and The New York Times. Overall, 2,977 clauses were analysed both qualitatively, to find out the reason of occurrence, and quantitatively, to determine the frequency of occurrence for each microstrategy. Evidentiality, Hyperbole, Metaphor, National Self-Glorification, Negative Lexicalisation, and Number Game were the most frequent micro-strategies. Such high frequencies of the strategies can make for effective discursive apparatus to make readers believe what news articles claim is true. The most salient implication of this study would be raising readers’ and academics’ awareness of the need to view news articles critically to avoid negative ramifications of ideological propagandas. In the same vein, newspapers need to be cognizant of the micro-strategies they consciously or sub-consciously employ since certain micro-strategies can be used to manipulate readers’ minds and help news agencies to feed their readers certain ideological and political agendas.